Implementasi Projek Penguatan Profil Pelajar Pancasila untuk Pengembangan Karakter Siswa di SDN Tlogosari Kulon 01 Kota Semarang - Ahmad Ishaqie Wahdhany; Mira Azizah; Ariani Nur Setyawati (Departement of Mathematics Education, 2024)
This research aims to determine the implementation of the Pancasila Student Profile Strengthening Project Program in the Independent Learning Curriculum in the Character Development of Students at SDN Tlogosari Kulon 01. This research is included in the qualitative research category using a descriptive analysis approach. The data collection technique is carried out through three series of activities, namely observation, interviews and documentation. The results of the research show that the implementation of the Project Program for Strengthening Pancasila Student Profiles in the Independent Learning Curriculum in Student Character Development at SDN Tlogosari Kulon 01 is going well.